Development of a physically-based model using deterministic approach for landslide prediction - Agcaoili, Elaine C.; Ventura, Giancarlo P.
Recently, the assessment of landslide hazards has been one of the main concerns in the field of disaster risk and mitigation because a multitude of areas in the country are prone to rainfall-induced landslides. By using the deterministic approach of landslide prediction involving slope stability simulation which results from the calculation of the factor of safety, the study is aimed to develop a physically-based model that consists of a methodology that combines the groundwater model for analyzing the pore-water pressure and the infinite slope stability model for computing the factor of safety. The seepage analyses were implemented using SEEP/W 2-D finite element software. A parametric study was conducted wherein, the model takes into account the behavior of the pore-water pressures by including the hydraulic properties of the soil, the slope geometry and the physical processes relating the rainfall regime to the groundwater level fluctuations. Analysis of a site subjected to a heavy rainfall in Antipolo, Rizal was then investigated to assess the landslide risk in the area. Results of the site-specific study show that upon application of an antecedent infiltration rate of 3.82 x 10-4 m/hr and a subsequent rainfall flux contributed by the southwest monsoon in August 2013 as a function of time for S days, the factors of safety for various depth failures namely: on the surface (Om), O.Sm , 1.0m and 2.0m remained greater than unity signifying that the slope remained stable throughout the entire S-day rainfall duration. The minimum rainfall intensity to cause a landslide in the site was then identified. It has been found out that at least 0.0063 m/hr of rainfall is needed for the site to fail within 48 to 72 hours of the rainfall event. Also, an extreme case of 0.01 m/hr is necessary for failure to occur within the first 24 hours. Modeling of the site through ArcGIS show the sanle patterns for varying depth failures. The model reveals that the bottom portion of the site is the most critical and most prone to slope failure. The model is consistent with the numerical computations done. Other values of the factor of safety are different in the model since the model used the actual values of the slope provided by the Digital Elevation Model. Thus, the factors of safety were computed per 10m grid. Nonetheless, the rest of the area should not be disregarded since the values of the factor of safety are just close to one. The research that has been undertaken has expound and analyzed a number of issues that would be beneficial to the advancement of quantitative landslide hazard assessment and prediction.